Pore structure and thermal oxidation curing behavior of porous polymer derived ceramics with superhigh porosity fabricated by freeze casting. Issue 22 (15th November 2021) - Li, Fuping; Zhao, Linna; Dang, Wei; Xu, Zhuoli; Zhao, Kang; Xue, Mengjiao; Tang, Yufei
Abstract: Porous ceramics with porosity up to 92.5 % have been successfully fabricated by freeze casting of polycarbosilane (PCS) solution. The effect of PCS concentration and thermal oxidation curing on the pore structure and compressive properties was investigated. Curing mechanism and thermodynamics were illuminated through analyzing the molecular structure, curing activation energy, and curing degree. Porous ceramics, mainly composed of SiC and a small amount of SiO2, have dendritic pore structure which well replicates the solidification morphology of camphene solvent. Results of FT-IR and Gaussian computation of PCS electron density show that Si–H and Si–CH3 bonds play a dominant role in thermal oxidation curing reaction. Both curing degree and ceramic yield increase with the increase in curing temperature and time. The curing degree of Si–H bond is close to 52 % and the corresponding ceramic yield is about 83 % when the porous PCS was cured at 200 °C for 90 min. Both polymer concentration and curing time have influences on the compressive strength of porous ceramics.